Fabrication of a leaf-like superhydrophobic CuO coating on 6061Al with good self-cleaning, mechanical and chemical stability. Issue 10 (July 2020) - Lv, Zhexin; Yu, Sirong; Song, Kaixing; Zhou, Xue; Yin, Xiaoli
Abstract: Copper oxide is widely used to obtain superhydrophobic surfaces due to its special micro/nano-structures and properties. However, there are few studies on a leaf-like CuO superhydrophobic coating by direct thermal oxidation of Cu on 6061Al substrate. In this work, there is a simple and low-cost method including chemical replacement, thermal oxidation and low-energy-modification with stearic acid. The resultant coating is superhydrophobic and oleophilic with water contact and sliding angles of 157 . 3 ∘ ± 0 . 5 ∘ and 3 . 6 ∘ ± 1 ∘, respectively. Additionally, it has low adhesion and excellent self-cleaning performances, whose corresponding mechanical analyses are conducted to theoretically discuss that stable micro/nano-structures and trapped air pockets could effectively influence the interfacial adhesion. Importantly, after tape-peeling, sandpaper-abrasion, and chemical stability tests, the coating still keeps superhydrophobic. Especially, in 3.5 wt% NaCl aqueous solution, compared with the corrosion current density of bare 6061Al substrate ( 7.18 × 10 − 7 A / cm 2 ), that of the SHP CuO coating ( 0.77 × 10 − 7 A / cm 2 ) decreases obviously. In sum, the method is especially suitable for large-scale industrial production of a stable superhydrophobic coating on Al alloys. Graphical abstract: Image 1 Highlights: Leaf-like SHP CuO coating on 6061Al is fabricated by direct thermal oxidation. Self-cleaning process on the SHP CuO coating is analyzed from the force perspective. SHP CuO coating exhibits low-adhesion and good self-cleaning, mechanical stability and corrosion resistance.